2007
DOI: 10.1016/j.bbamem.2007.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ceramide N-acyl chain and polar headgroup structure on the properties of ordered lipid domains (lipid rafts)

Abstract: Ceramides are sphingolipids that greatly stabilize ordered membrane domains (lipid rafts), and displace cholesterol from them. Ceramide-rich rafts have been implicated in diverse biological processes. Because ceramide analogues have been useful for probing the biological function of ceramide, and may have biomedical applications, it is important to characterize how ceramide structure affects membrane properties, including lipid raft stability and composition. In this report, fluorescence quenching assays were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 54 publications
7
58
0
Order By: Relevance
“…1C) analyses revealed a dosedependent increase in cell surface ceramide levels in U266 cells following EGCG treatment. Displacement of cholesterol from the lipid raft on the plasma membrane occurs after generation of ceramide by ASM (17), and EGCG has been shown to induce disruption of cholesterol-rich lipid rafts in colon cancer cells (27). Therefore, we next investigated the involvement of ASM in EGCGinduced disruption of lipid raft domains by staining with the lipid-mimetic dialkyl-indocarbocyanine (DilC16) and using a cold Triton X-100 solubility assay ( Fig.…”
Section: Activated Asm Induces Lipid Raft Disruptionmentioning
confidence: 99%
See 1 more Smart Citation
“…1C) analyses revealed a dosedependent increase in cell surface ceramide levels in U266 cells following EGCG treatment. Displacement of cholesterol from the lipid raft on the plasma membrane occurs after generation of ceramide by ASM (17), and EGCG has been shown to induce disruption of cholesterol-rich lipid rafts in colon cancer cells (27). Therefore, we next investigated the involvement of ASM in EGCGinduced disruption of lipid raft domains by staining with the lipid-mimetic dialkyl-indocarbocyanine (DilC16) and using a cold Triton X-100 solubility assay ( Fig.…”
Section: Activated Asm Induces Lipid Raft Disruptionmentioning
confidence: 99%
“…In addition, ASMinduced generation of ceramide leads to displacement of cholesterol from lipid rafts on the plasma membrane (17). However, whether ASM influences cholesterol-rich lipid raft formation, which is associated with receptor tyrosine kinase (RTK) activation (18), is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The first is ceramide chain heterogeneity (ESM is 84% C 16 and 16% longer saturated chains); the ability of ceramides to stabilize liquid-ordered phases and to form gel phase domains has been shown to depend on chain length (Chiantia et al, 2007;Megha et al, 2007;Fig. 7.…”
Section: Membrane Restructuringmentioning
confidence: 99%
“…Ceramide has also been shown to displace cholesterol from raft domains in model and cellular membranes (Ali et al, 2006;Chiantia et al, 2006;Megha and London, 2004;Megha et al, 2006;Yu et al, 2005b). Several recent studies have concluded that the ability of ceramide to modulate the properties of liquid-ordered domains and form ceramide-enriched gel domains is affected by the chain length and that short-chain ceramides (<C 12 ) are not good models for studies of the biological activity of ceramide (Chiantia et al, 2007;Megha et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In general, liquid ordered domains are thicker than the surrounding liquiddisordered membrane. Moreover, long saturated fatty acyl tails have been shown to be a prerequisite for the association between sphingolipid rafts and glycophosphatidylinositol (GPI)-anchored proteins (Benting et al, 1999;Megha et al, 2007). A proposed offshoot of such protein-lipid mismatching interactions is that integral membrane proteins might be key determinants of membrane thickness.…”
Section: Introductionmentioning
confidence: 99%